2018
DOI: 10.1017/sjp.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chinese Teachers’ Stress Coping Ability through Group Sandplay

Abstract: Teachers are burdened by high work pressure, suggesting the need for an effective stress coping system to support them. The present study evaluated the effectiveness of coping strategies currently utilized by teachers and explored the potential contribution of group sandplay to coping. The study was led by a group of experienced therapists and sandplay practitioners. Two hundred teachers served as participants, equally divided into two groups: An experimental sandplay group (EG) and control group. Both groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Dahal and Pradhan 2018 [43] Nepal (Asia) Non-RCT This review found 40 articles with sixteen types of interventions for addressing burnout and stress in teachers: (a) 18 studies on mindfulness-based interventions [12,[23][24][25]27,29,[33][34][35][36][37][38][39][40][41] including in combination with yoga [32] or in combination with Cognitive Behavioural Therapy (CBT) [26,42], (b) seven studies reported on CBT only [30,31] or CBT in combination with yoga [22,28], or other derivatives, e.g., Inquiry-Based Stress Reduction (IBSR) [57,60] and Cyclic meditation [43] (c) seven studies used Rational Emotive Behavior Therapy [44][45][46][47][48][49][50], (d) one study on Sports-Based Physical Activity Program [55] (e) Christian prayer and prayer-reflection [52] (f) Group Sandplay [58], (g) stress reduction training (e.g., Stress Management and Resiliency Training Program (SMART) [51], Autogenic Training [59], Progressive Muscle Relaxation with music and aromatherapy [53]), and (h) interventions focusing on building social and emotional competence (e.g., A+ intervention [56], Ability Model of Emotional intelligence…”
Section: Interventions To Reduce Stress and Burnout Among Teachersmentioning
confidence: 99%
“…Dahal and Pradhan 2018 [43] Nepal (Asia) Non-RCT This review found 40 articles with sixteen types of interventions for addressing burnout and stress in teachers: (a) 18 studies on mindfulness-based interventions [12,[23][24][25]27,29,[33][34][35][36][37][38][39][40][41] including in combination with yoga [32] or in combination with Cognitive Behavioural Therapy (CBT) [26,42], (b) seven studies reported on CBT only [30,31] or CBT in combination with yoga [22,28], or other derivatives, e.g., Inquiry-Based Stress Reduction (IBSR) [57,60] and Cyclic meditation [43] (c) seven studies used Rational Emotive Behavior Therapy [44][45][46][47][48][49][50], (d) one study on Sports-Based Physical Activity Program [55] (e) Christian prayer and prayer-reflection [52] (f) Group Sandplay [58], (g) stress reduction training (e.g., Stress Management and Resiliency Training Program (SMART) [51], Autogenic Training [59], Progressive Muscle Relaxation with music and aromatherapy [53]), and (h) interventions focusing on building social and emotional competence (e.g., A+ intervention [56], Ability Model of Emotional intelligence…”
Section: Interventions To Reduce Stress and Burnout Among Teachersmentioning
confidence: 99%
“…Previous research revealed that hindrance job stress reduces performance [6], job satisfaction [2], and employee engagement [7]. Too much job stress can contribute to burnout, frustration, anxiety, depression, and other psychophysical health illnesses [8]. Depersonalization in the workplace is commonly considered a component of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…All these parties have their own expectations which, more often than not, are in conflict with each other, resulting in schoolteachers facing multiple challenges and job demands in the course of their teaching career [3]. It has been revealed that most stressors teachers face come from a competitive societal environment, heavy workload, pupil behavior, time demands, work conditions, staff relationships, and family responsibilities [5]. Certain levels and types of job stress are undoubtedly instrumental in triggering teachers' motivations and generating better teaching performance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, when exceeding organizational and/or personal resources, job stress may have deleterious consequences both to educational objectives and on teachers themselves, ultimately compromising other parties' interests and well-being [8]. For example, too much stress contributes to serious psychological disorders such as job burnout, anger, frustration, anxiety, depression, and nervousness [5] as well as physical health issues such as headache, dizziness, neck pain, and sleeping problems [9]. In Spain, scholars have revealed that stressors perceived by schoolteachers hamper them from fully meeting learning objectives and cause burnout, anxiety, and depression [10,11].…”
Section: Introductionmentioning
confidence: 99%